2021
DOI: 10.1186/s12920-020-00855-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between CDKN2B/CDKN2B-AS1 gene polymorphisms with primary glaucoma in a North Indian cohort: an original study and an updated meta-analysis

Abstract: Background Variants in CDKN2B/CDKN2B-AS1 have been reported to modulate glaucoma risk in several GWAS across different populations. CDKN2B/CDKN2A encodes tumor suppressor proteins p16INK4A/p15INK4B which influences cell proliferation/senescence in RGCs, the degeneration of which is a risk factor for glaucoma. CDKN2B-AS1 codes a long non-coding RNA in antisense direction and is involved in influencing nearby CDKN2A/CDKN2B via regulatory mechanisms. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…As the first use case, we studied the target genes and pathway networks of CDKN2B-AS1, a gene that has been previously described in humans and associated with various functions [87,88]. CDKN2B-AS1 is involved in a large number of pathways, as shown in Figure 3A, including ‘Human immunodeficiency virus 1 infection’ and ‘coronavirus disease-COVID-19’.…”
Section: Resultsmentioning
confidence: 99%
“…As the first use case, we studied the target genes and pathway networks of CDKN2B-AS1, a gene that has been previously described in humans and associated with various functions [87,88]. CDKN2B-AS1 is involved in a large number of pathways, as shown in Figure 3A, including ‘Human immunodeficiency virus 1 infection’ and ‘coronavirus disease-COVID-19’.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, other three pan HDAC inhibitors are being studied in MPM patients (NCT00365053, Nct00128102 and NCT00535951). 44 In addition, there are also many biomarker-related experiments that have been proved to be related to the occurrence and development of MPM. A study using bioinformatics tools demonstrated that EZH2 and HMMR were found over-expressed in MPM tissues and the patients with elevated EZH2 and HMMR expressions had poor overall survival.…”
Section: Biomarkers For Mpmmentioning
confidence: 99%
“…LR is a statistical ML model which models a set of input features (X: input) into target variables (Y: output) by means of a sigmoid function which is an 'S' shaped curve and restricts Y in the range of 0 and 1 (De Cock et al, 2021). Sigmoid function σ : R −→ (0,1) is defined as:…”
Section: Logistic Regressionmentioning
confidence: 99%